Marital Dissolution of Parents: Perceived Psychological Effects on Young Adults into Romantic Relationships Among 18-25 Years Old Residing in Barangay 175 And 176, Caloocan City: Vol.3, No.1C (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study focused on the effects of parents' marital dissolution on young adults ages 18-25 and defined the effect of their romantic relationship. Fifty respondents from Barangay 175 and 176 Caloocan City were selected using purposive quota sampling based on specific characteristics or traits and implemented quotas for research samples to be helpful in data collection. This study employed descriptive research design to accurately and systematically describe a population, situation or phenomenon. It describes the respondents' profiles and determines the mental, emotional, and social effects. It also defined the effect on young adults regarding their romantic relationships and described the noticeable behavioural changes in a child's educational performance.   This study revealed that in terms of the demographic profile of respondents, females, with 70% of ages 20-21 years old, and 40 % of those who experienced marital separation of parents showed a great effect in terms of emotional and psychological well-being. It also shows that setting a high standard affects young adults in their romantic relationships. In addition, it has effects on their difficulty in studies.  Thus, the study recommended that young adults focus on their decisions so they can have contentment and no doubts about their relationship and partner’s trust. Teachers and parents should oversee and contact children who have seen noticeable behavioral changes in their studies. They should also give the guidance and counselling they require to be motivated to continue their studies.